Arsenic biotransformation potential of microbial arsH responses in the biogeochemical cycling of arsenic-contaminated groundwater. (January 2018) - Chang, Jin-Soo; Yoon, In-Ho; Kim, Kyoung-Woong
Abstract: ArsH encodes an oxidoreductase, an NAD(P)H-dependent mononucleotide reductase, with an unknown function, frequently within an ars operon, and is widely distributed in bacteria. Novel arsenite-oxidizing bacteria have been isolated from arsenic-contaminated groundwater and surface soil in Vietnam. We found that ArsH gene activity, with arsenite oxidase in the periplasm; it revealed arsenic oxidation potential of the ars H system. Batch experiment results revealed Citrobacter freundii strain VTan4 (DQ481466) and Pseudomonas putida strain VTw33 (DQ481482) completely oxidized 1 mM of arsenite to arsenate within 30–50 h. High concentrations of arsenic were detected in groundwater and surrounding soil obtained from Vinh Tru village in Ha Nam province (groundwater: 11.0 μg/L to 37.0 μg/L; and soil: 2.5 mg/kg, 390.1 mg/kg), respectively. An ars H gene encoding an organoarsenical oxidase protein was observed in arsenite-oxidizing Citrobacter freundii strain VTan4 (DQ481466), whereas ars B, ars H, and ars H were detected in Pseudomonas putida strain VTw33 (DQ481482). ars H gene in bacteria was first reported from Vietnam for resistance and arsenite oxidase. We proposed that residues, Ser 43, Arg 45, Ser 48, and Tyr 49 are required for arsenic binding and activation of ars H. The ars -mediated biotransformation strongly influenced potential arsenite oxidase enzyme of the operon encoding a homogeneous ars H. Results suggest that the further study of arsenite-oxidizing bacteria may lead to a better understanding of arsenite oxidase responses, such as those of ars H, that may be applied to control biochemical properties; for example, speciation, detoxification, bioremediation, biotransformation, and mobilization of arsenic in contaminated groundwater. Graphical abstract: Image 1 Highlights: Natural state of ars H genes could beinvolved in arsenic biogeochemical cycling. ars Hgene in bacteria was firstly reported from Vietnam form resistance andarsenite oxidase. ars genotypedisplaying microbial arsenic transformation in bacteria was evaluated in Vietnam. Pseudomonas putida strain VTw33 completely oxidized 1 mM of As (III) to As (V) within 30 h.